1981
DOI: 10.1121/1.385578
|View full text |Cite
|
Sign up to set email alerts
|

A neural-counting model incorporating refractoriness and spread of excitation. II. Application to loudness estimation

Abstract: In previous paper [Teich and Lachs, J. Acoust. Soc. Am 66, 1738--1749 (1979)] we demonstrated that an energy-based neural counting model incorporating refractoriness and spread of excitation satisfactorily described the results of pure-tone intensity discrimination experiments. In this paper, we show that the identical linear filter refractoriness model (LFRM) also provides proper results for pure-tone loudness estimation experiments at all stimulus levels. In particular, as the stimulus intensity increases fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…In Part II [2] we showed that the same linear filter refractoriness model (LFRM) also provided satisfactory results for fitting data obtained in pure-tone loudness estimation experiments. In Part III [3] we considered intensity discrimination and loudness summation for variable-bandwidth noise stimuli and demonstrated once again that the LFRM calculations were in accord with the trends of the data.…”
Section: Introductionmentioning
confidence: 92%
“…In Part II [2] we showed that the same linear filter refractoriness model (LFRM) also provided satisfactory results for fitting data obtained in pure-tone loudness estimation experiments. In Part III [3] we considered intensity discrimination and loudness summation for variable-bandwidth noise stimuli and demonstrated once again that the LFRM calculations were in accord with the trends of the data.…”
Section: Introductionmentioning
confidence: 92%
“…3 The effects of a masker on hearing thresholds (left masked hearing level) on the acoustic reflex (middle) and loudness (right) for a representative case with simulated hearing loss tion at the level of acoustic nerve fibers or of the lower brain stem plays an important role as an input eliciting the AR and constituting the basis for loudness at the level of the ART. It is hypothesized that an increase in the spike rate of each fiber and the spread of excitation through the cochlea could play an important role in loudness [5,13,18]. The same kind of mechanism is also suggested as a trigger input of the AR [2,12].…”
Section: Discussionmentioning
confidence: 99%
“…Ages ranged from 14 to 69 years, with a mean age of 44.5 years. Etiologies of deafness included sudden deafness [13], Meniere's disease [1], acoustic tumors [4], other retrocochlear lesions [3] and idiopathic causes [10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) for the photon-counting detection of chaotic radiation of arbitrary spectrum is straightforward, since the first-order statistics do not depend on the spectrum. It is well-known that for linearly polarized chaotic radiation incident upon a detector substantially smaller than the coherence area, the probability density function for the rate X is given by (17) where X is the average value of X. By using Eq.…”
Section: Dead-time-modified Mean For Chaotic Radiationmentioning
confidence: 99%